2022
DOI: 10.56275/fitovida.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de sustrato orgánico en crecimiento de plantulas de bolaina blanca (Guazuma crinita Mart.) y shaina (Colubrina glandulosa Perkins.) en fase de vivero – San Martin, 2022

Abstract: Al determinar el efecto de sustrato orgánico en el crecimiento de plántulas bolaina blanca (Guazuma crinita) y shaina (Columbrina glandulosa Perkins.) en fase de vivero en el Fundo San Jorge distrito de Zapatero, provincia de Lamas – San Martín, Perú. El sustrato utilizado fue (tierra negra, cascarilla carbonizada, compostada y gallinaza). Se determinó el incremento de altura total, diámetro del tallo, longitud de raíz, volumen del sistema radicular y número de hojas de dos especies forestales bolaina blanca (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the case of tropical native species, an extensive review by 17 summarizes that most species in the tropics demand nutrients in the order N > K > Ca > Mg > P and that concentrations of nutrients on the litter are higher in Ca and N and higher in deciduous species in comparison to evergreen species. In the case of Guazuma crinita, few studies on nutrition or fertilizer requirements exist; most are related to the response to organic and inorganic fertilizers in greenhouse 22 and field conditions [23][24][25] , where all the authors found positive responses for biometric measurements (height, diameter, dry weight, foliar area, root growth) when fertilizers or amendments were used. From these studies, only 22,24 analyzed foliar concentration of nutrients, but only for N, P and K, where they reported concentrations of nutrients in the order N > K > P.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tropical native species, an extensive review by 17 summarizes that most species in the tropics demand nutrients in the order N > K > Ca > Mg > P and that concentrations of nutrients on the litter are higher in Ca and N and higher in deciduous species in comparison to evergreen species. In the case of Guazuma crinita, few studies on nutrition or fertilizer requirements exist; most are related to the response to organic and inorganic fertilizers in greenhouse 22 and field conditions [23][24][25] , where all the authors found positive responses for biometric measurements (height, diameter, dry weight, foliar area, root growth) when fertilizers or amendments were used. From these studies, only 22,24 analyzed foliar concentration of nutrients, but only for N, P and K, where they reported concentrations of nutrients in the order N > K > P.…”
mentioning
confidence: 99%
“…In the case of Guazuma crinita, few studies on nutrition or fertilizer requirements exist; most are related to the response to organic and inorganic fertilizers in greenhouse 22 and field conditions [23][24][25] , where all the authors found positive responses for biometric measurements (height, diameter, dry weight, foliar area, root growth) when fertilizers or amendments were used. From these studies, only 22,24 analyzed foliar concentration of nutrients, but only for N, P and K, where they reported concentrations of nutrients in the order N > K > P.…”
mentioning
confidence: 99%